KARAKTERISTIK TUTORIAL ONLINE PERKEMBANGAN TUMBUHAN BERBASIS MASALAH DENGAN SIKLUS REFLEKTIF GIBBS DAN EPORTFOLIO PADA MATA KULIAH PERKEMBANGAN TUMBUHAN - Sekawinahyu, Mestika; Rustaman, Nuryani Y.; Widodo, Ari; Riandi, Riandi (Jurnal BIOEDUIN, 2019)
Reflective thinking skill is needed by prospective and in-service teachers. Plant Development online tutorial program based on problems with Gibbs reflective cycles and eportfolio that aim to develop reflective thinking skills of biology education students who follow online tutorials Plant development has been developed through several stages. To find out how the characteristics of the program, a study was conducted on the results of the program trials. In this program, students’ reflective thinking skills are honed through reflection activities using the Gibbs reflective cycle which is preceded by problem-based learning activities. Students can do activities and tasks given by the program freely, but still in the control carried out by the system in the form of navigation. The program has flexibility in the pace of student learning, but it still pays attention to the integrity of online tutorial activities and tasks done by students. From the From the study, it was found that the program has three main characteristics, namely 1) honing students’ reflective thinking skills, 2) controlling, and 3) having a flexible system based on student learning pace.